2020
DOI: 10.1002/ajoc.202000156
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phenanthro[9,10‐d]imidazoles and their Potential Applications in Solution Processable Bottom‐Gated OFETs

Abstract: Phenanthro[9,imidazole is synthesized by employing Radziszewski method and further functionalized through palladium catalyzed Suzuki cross-coupling reaction. Solution processable organic field-effect transistors (OFETs) are assembled in bottom gate-top contact architecture. A binary solvent system comprising of chloroform/toluene in the ratio of 1/1 is preferred for the deposition of active semiconducting layer. The fabricated devices demonstrated excellent p-type characteristics with a good mobility, high ON/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The top contact ensures the uniform orientation of the active layer over dielectric layer where in the bottom contact devices, the orientation over electrodes and dielectric layer varies and thus disturbs the charge carrier movement. Therefore, minimum contact resistance is obtained in BGTC architecture 52 . The fabricated devices were characterized in ambient conditions; threshold voltage (V TH ) and charge carrier mobility (µ) were obtained from the intercept and slope of the linear plot of the square root of drain to source current (I DS 1/2 ) versus the gate voltage.…”
Section: Resultsmentioning
confidence: 99%
“…The top contact ensures the uniform orientation of the active layer over dielectric layer where in the bottom contact devices, the orientation over electrodes and dielectric layer varies and thus disturbs the charge carrier movement. Therefore, minimum contact resistance is obtained in BGTC architecture 52 . The fabricated devices were characterized in ambient conditions; threshold voltage (V TH ) and charge carrier mobility (µ) were obtained from the intercept and slope of the linear plot of the square root of drain to source current (I DS 1/2 ) versus the gate voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Tonzola et al and Kuo et al employed oligoquinoline and imidazole, respectively, for electron-transport properties to improve the efficiency of the device. Moreover, it is also observed that in a molecular framework, PI as an electron-deficient unit significantly enhances electron injection and transport ability. , Our recent work demonstrated that structural tailoring of PI resulted in good OFET behavior . Based on these considerations, we functionalized PI with the incorporation of electron-donating and -accepting groups to facilitate the balance of charge carriers and hence enhance the device performance.…”
Section: Introductionmentioning
confidence: 98%
“…29,30 Our recent work demonstrated that structural tailoring of PI resulted in good OFET behavior. 35 Based on these considerations, we functionalized PI with the incorporation of electron-donating and -accepting groups to facilitate the balance of charge carriers and hence enhance the device performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Phenanthroimidazole derivatives exhibit a rigid-planar-conjugate structure and ambipolar characteristics owing to the bonding structures of the two nitrogen atoms of the imidazole ring. 17,18 These derivatives have been widely employed as blue light-emitting materials based on their high carrier mobilities and conductivities, high triplet energies, and high fluorescent efficiencies. [19][20][21] Therefore, the phenanthroimidazole unit is a good candidate for the fabrication of COFs.…”
Section: Introductionmentioning
confidence: 99%